Efficacy of preoperative testosterone therapy in hypospadias: a systematic review and meta-analysis - Gozali Sembiring (SpringerOpen, 2021)
Abstract Background Bleeding, hematoma, edema, wound infection, and scar formation are the common problems linked with hypospadias reconstruction. Hormone treatment is recommended before surgical treatment to improve intraoperative circumstances. However, no meta-analysis has explored the effectiveness and side effects of testosterone treatment before surgery in hypospadias. Main body of the abstract The purpose of this paperwork is to evaluate the impact of preoperative testosterone treatment in hypospadias based on clinical data from published trials. This study searched MEDLINE, Science Direct, and the Cochrane Library without regard to year. However, only English journals were included, with a manual search using the Preferred Reporting Items for Systematic Reviews and Meta-analysis of Observational Studies in Epidemiology Guidelines supplementing the search. In this meta-analysis, five papers were considered. Two of these investigations were multicenter randomized clinical trials. Two of the studies were prospective, with a median follow-up of varying lengths. A retrospective investigation was conducted. There were 585 patients in all that took part in this trial. After surgery, the complication rate was measured in both the intervention and control groups, including meatal stenosis, fistula, glans dehiscence, scarring, reoperation rate, urethral diverticulum, fine pubic hair, and sexual precocity. The only significant difference between the intervention and control groups was that the intervention group had a decreased frequency of glans dehiscence following surgery (OR 0.40 with the 95% CI of 0.17 until 0.97). Conclusions This study discovered that a patient who got testosterone before surgery had a considerably decreased complication risk for glandular dehiscence. Reoperation rate, urethral-cutaneous fistula, meatal stenosis, and penile scarring in children with hypospadias, on the other hand, revealed no significant difference in the testosterone-treated group against the control group.